Multi-objective topology optimization of cold plates for enhanced battery thermal management in electric vehicles - Yijun Wang; Minghao Yu; Haiyang Fan; Jae Dong Chung (Case Studies in Thermal Engineering)
Efficient thermal management is critical for maintaining the performance, longevity, and safety of lithium-ion batteries, particularly in electric vehicles (EVs). This paper presents a multi-objective topology optimization (TO) approach for designing cold plates in battery thermal management systems (BTMS), with the aim of minimizing both average temperature and power dissipation. The TO model was benchmarked against two established designs: a straight-channel baseline model and the serpentine-channel cold plate used in the GM Volt EV. The optimized TO design exhibited an 82 % reduction in friction factor at Re = 100 and a 75.6 % reduction at Re = 2100, compared to the GM model. Additionally, the TO model's Performance Evaluation Criterion (PEC) was approximately 58 % higher than that of the baseline design and 15 % higher than the GM model at Re = 2100, indicating a superior balance of thermal and hydraulic performance. These results underscore the potential of topology optimization to enhance the design of cold plates for BTMS, offering improved efficiency and effectiveness for high-power applications in EVs.